GAYA HIDUP PUNKLUNG (Studi Kasus pada Komunitas Punklung di Cicalengka, Bandung) - Tri Esti Budiningsih; Didit Setiawan (Universitas Negeri Makassar, 2015)
This study aimed to know the lifestyle punklung in Cicalengka Bandung. Subjects of research were Punklung community. Methods of data collection using participant observation, interviews (the spokesman for the community and some members of the Punklung community). Research results presented in descriptive qualitative showed that punklung’s lifestyle is influenced by several factors which are, attitudes, experiences and observations, motive, group’s reference, and cultural transformation. Punklung lifestyle oriented to arts, namely music. Judging from the activity, they formed a band group, despite the stigma that exists in society considers negative assumption about punk kids, but there is also a punk kid whose life clean of negative things, punk Kids have a positive view of themselves and others. Key factors which driving young people to join the community of the greatest punk because of the encouragement of it in those who want to be punk or having a like to punk because of their great interest towards punk which is used as a medium for self-expression and as a search for their own identity. Factors outside their milieu that they were mostly children punk.